Correlation between third molar mineralization and chronological age by three methods - Esther Carneiro Ribeiro; Luis Ferreira de Sousa Filho; Clarissa Araújo Campos Camelo; José Cadmo Wanderley Peregrino de Araújo Filho; Renata de Oliveira Guaré; Camila Helena Machado da Costa; Manuella Santos Carneiro Almeida (Editorial Ciencias Médicas, 2018)
Introduction: dental mineralization stages have been used in several studies to estimate age, and the results obtained have been found to be reliable. Objective: correlate third molar mineralization and chronological age using the methods developed by Nolla, Demirjian, and Nicodemo, Moraes and Medici Filho in a population sample from Northeast Brazil. Methods: of a total 1 205 digital panoramic radiographs, 297 were selected of patients routinely seen in a private dental radiology service. All the images underwent darkroom evaluation by three qualified examiners using the methods developed by Nolla (1960), Demirjian (1973), and Nicodemo, Moraes and Medici Filho (1974). Numerical data were summarized by location and dispersion descriptive statistics. For statistical analysis a simple linear regression model was adjusted which considered age as response variable. A significance level of 5 % was adopted for the tests. Results: third molar development occurred earlier in males in most stages by the three methods. In upper teeth, sexual dimorphism was more evident in Nolla stage "7" (difference of 16.34 m in tooth 18 and 14.43 m in tooth 28). In lower teeth, the greatest differences occurred in Nolla stage "6" (difference of 13.92 m in 38 and 10.46 m in 48) and Nicodemo stage "5" (difference of 16.23 m higher in tooth 38 and 9.9 m in 48). Third molar development was similar on the right and left sides, but greater in upper teeth than in lower teeth. The study allowed development of linear regression formulas based on the three methods proposed, making it possible to estimate the chronological age of the individuals in the sample. Conclusions: the three methods found a correlation between third molar development and chronological age.